Evaluation of marketing channel options for guava in Kota district of Rajasthan - Bairwa, Kailash Chand; Sharma, Rajesh; Sharma, Madhu (Annals of Agricultural Research, 2014)
Guava (Psidium guajava L.) is one of the most important commercial fruit crops in India. The present study explores price spread for guava through different marketing channels. The multi-stage sampling procedure was followed to collect primary data from 200 farmers and traders during 2005-06. Therefore, different marketing channels (local and distant) were identified in marketing of guava. The large share of the produce was sold through pre- harvest contractor to distant terminal market. The net share of wholesalers was highest in channel-III. The analysis of price spread revealed that price spread was lowest in channel-III. Therefore, channel-III was the most remunerative channel for farmers in local markets The study suggested that there should be agro-processing industries in the district, sound market intelligence system so that information regarding price prevailing in different local and distant markets can be made available to farmers.